PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU MELALUI DISIPLIN KERJA GURU DI SMK PANCA DHARMA BALIKPAPAN - Alexander, Feby Yohannes (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
This study aims to determine the effect of the principal's transformational leadership style and organizational culture on teacher performance through teacher work discipline at SMK Panca Dharma Balikpapan. The population in this study were all teachers of SMK Panca Dharma Balikpapan with a sample of 40 respondents with saturated sampling technique. Data collection techniques used by distributing questionnaires and documentation. The data analysis method used is descriptive statistical analysis and Partial Least Square (PLS). The results showed that the principal's transformational leadership style had an effect on work discipline, organizational culture had an effect on work discipline, the principal's transformational leadership style had an effect on teacher performance, organizational culture had no effect on teacher performance, work discipline had an effect on teacher performance, and the principal's transformational leadership style does not have an indirect effect on teacher performance through work discipline, and organizational culture has an indirect effect on teacher performance through teacher work discipline.